Specialist perioperative allergy clinic services in the UK 2018: Results from the Royal College of Anaesthetists Sixth National Audit Project (NAP6) investigation of perioperative anaphylaxis. Issue 7 (19th June 2018) - Egner, W.; Cook, T. M.; Garcez, T.; Marinho, S.; Kemp, H.; Lucas, D. N.; Floss, K.; Farooque, S.; Torevell, H.; Thomas, M.; Ferguson, K.; Nasser, S.; et al.
Summary: Background: The Royal College of Anaesthetists 6th National Audit Project examined Grade 3‐5 perioperative anaphylaxis for 1 year in the UK. Objective: To describe the causes and investigation of anaphylaxis in the NAP6 cohort, in relation to published guidance and previous baseline survey results. Methods: We used a secure registry to gather details of Grade 3‐5 perioperative anaphylaxis. Anonymous reports were aggregated for analysis and reviewed in detail. Panel consensus diagnosis, reaction grade, review of investigations and clinic assessment are reported and compared to the prior NAP6 baseline clinic survey. Results: A total of 266 cases met inclusion criteria between November 2015 and 2016, detailing reactions and investigations. One hundred and ninety‐two of 266 (72%) had anaphylaxis with a trigger identified, of which 140/192 (75%) met NAP6 criteria for IgE‐mediated allergic anaphylaxis, 13% lacking evidence of positive IgE tests were labelled "non‐allergic anaphylaxis". 3% were non‐IgE‐mediated anaphylaxis. Adherence to guidance was similar to the baseline survey for waiting time for clinic assessment. However, lack of testing for chlorhexidine and latex, non‐harmonized testing practices and poor coverage of all possible culprits was confirmed. Challenge testing may be underused and many have unacceptably delayed assessments, even in urgent cases. Communication or information provision for patients was insufficient, especially for avoidance advice and communication of test results. Insufficient detail regarding skin test methods was available to draw conclusions regarding techniques. Conclusion and Clinical Relevance: Current clinical assessment in the UK is effective but harmonization of approach to testing, access to services and MHRA reporting is needed. Expert anaesthetist involvement should increase to optimize diagnostic yield and advice for future anaesthesia. Dynamic tryptase evaluation improves detection of tryptase release where peak tryptase is <14 μg/L and should be adopted. Standardized clinic reports containing appropriate details of tests, conclusions, avoidance, cross‐reactivity and suitable alternatives are required to ensure effective, safe future management options.